2021
DOI: 10.1186/s43014-021-00078-6
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic and adverse interplay of hypogeal germination periods on brown rice (Oryza sativa): nutrient and non-nutrient characteristics

Abstract: This study investigated the symbiotic and adverse consequence of hypogeal germination periods on nutrients and non-nutrient characteristics of brown rice (Oryza sativa). Brown rice paddy was subjected to hypogeal germination for 0–72 h using one-factor design-response surface methodology (OFD-RSM) and evaluated for nutrients and non-nutrient characteristics. The results showed that hypogeal germination caused a significant (p < 0.05) change in the proximate composition: protein (9.42–12.36%), fat (0.88–1.38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The significant increase (p < .01) in the mineral content of the GBR could be ascribed to that the germination process lowered phytic acid content which liberates bound minerals (Caceres et al, 2014a) and results in a higher mineral bioaccessibility. Chima and Fasuan (2021) noticed similar observations for GBR.…”
Section: Mineral Analysissupporting
confidence: 77%
“…The significant increase (p < .01) in the mineral content of the GBR could be ascribed to that the germination process lowered phytic acid content which liberates bound minerals (Caceres et al, 2014a) and results in a higher mineral bioaccessibility. Chima and Fasuan (2021) noticed similar observations for GBR.…”
Section: Mineral Analysissupporting
confidence: 77%
“…The subsequent decades brought many contributions to the current knowledge about phenolic compounds in wheat, rice, and their processing by-products, especially when it comes to unconventional cultivars, such as black, brown, red, and wild rice [ 110 , 111 , 112 ]. The database on flavonoids of rice, including proanthocyanidins, is shown in Table 2 .…”
Section: Phenolics Of Rice Wheat and Their Processing By-productsmentioning
confidence: 99%
“…Likewise, the phenolic profile of ancient and modern durum wheat genotypes was addressed by di Loreto et al [ 136 ]. Other groups have also conducted comparative studies [ 112 , 118 ], and old durum wheat cultivars have been suggested to offer unique phytochemical profiles that could render better health effects than those of modern durum wheat [ 131 ]. However, in terms of TPC, Tunisian durum wheat was ranked differently (modern > landraces > old) by Boukid et al [ 130 ].…”
Section: Phenolics Of Rice Wheat and Their Processing By-productsmentioning
confidence: 99%
“…Rice ( Oryza sativa ) is one of the world's top three food crops and feeds nearly 20% of the global population, playing a critical role in food security (Wu et al, 2023). It is a starchy food, being considered the most important cereal in developing countries (Chima & Fasuan, 2021). According to da Silva et al (2023), the high consumption of this cereal is linked not only to its nutritional value but also due to some particularities of this grain, such as not being an allergenic food and not being toxic for celiacs, making it suitable for the production of products without gluten.…”
Section: Introductionmentioning
confidence: 99%